Principal instructional leadership practice and its effect on teachers’ reflective practices: Indicators for best classroom practices - Amzat, Ismail Hussein (Routledge, 2017)
Instructional leadership is an old theory, but despite its age, the theory remains widely used with respect to teaching and learning. This chapter investigates the role of principal instructional leadership practices on teacher reflective practices by proposing model-based indicators for better reflection and practice for teaching generally in Malaysia and specifically among schoolteachers in northern Malaysia. Good school leadership practices have been reported to have a positive effect on teacher development and continuous learning. Good school leadership also has positive effects on teachers who are seeking more knowledge because principals can empower teachers to be more committed and to enhance their learning. This chapter uses a quantitative approach and distributed questionnaires to teachers in one of Malaysia's Northern States. The measurement model was used to identify whether items were related to their construct or whether the indicators were loaded under their respective latent variables.